The Effect of Gender Diversity and Investment Opportunities on Dividend Policy with Debt Policy as an Intervening Variable Lq-45 Indexed Companies Listed On Indonesia Stock Exchange - MIFTAHURRAHMAH (Universitas Negeri Padang, 2023)
This study aims to examine the influence of gender diversity with the presence of women on the board of directors and investment opportunities on dividend policies (dividend payments) mediated by debt policies. The population in this study is all LQ-45 companies listed on the Indonesia Stock Exchange in 2013-2020. The sampling technique uses a purposive sampling technique with a total sample of 199samples. The data used is secondary data. The data analysis method used is path analysis. The results of the study concluded that debt policy is only able to mediate the relationship between gender diversity and dividend policy. On the other hand, debt policy is unable to mediate the relationship between investment opportunities and dividend policy.